Description of a new species of Chrysina Kirby, 1828 (Coleoptera: Scarabaeidae: Rutelinae) from resplendens group, based on morphological characters and mtDNA COX I molecular marker - Zubov, A. S.; Ivshin, N. V.; Titarenko, A. Yu.; Andrianov, B. V. (Acta Biologica Sibirica, 2019)
A new species of the genus Chrysina Kirby, 1828 is decribed from Panama. Chrysina kalinini sp.n. is related to Chrysina resplendens (Boucard, 1875) in habitus, male genitalia morphology and mtDNA COX I molecular marker). The two closely related species differ in the shape of pronotum, mesosternal process and male genitalia. mtDNA COI molecular marker analysis gives a reliable distance for the compared species.